VALUASI EKONOMI FUNGSI HIDROLOGIS KAWASAN HUTAN LINDUNG GUNUNG GAWALISE SEBAGAI PENYEDIA KEBUTUHAN AIR BAGI MASYARAKAT DI WILAYAH KECAMATAN ULUJADI KOTA PALU - Budi, Hery Prastowo (Katalogis, 2017)
Forests function as a regulator of the water system, namely by holding rainwater to reduce surface erosion and absorb into the soil, so it can be used by the surrounding community. Forest functions in providing water must be taken into account with a specific calculation. That function is an hydrological functions of forests as providers of clean water needs. The calculation of the value of forest land are based on the calculation of the volume of produced water from the spring that is multiplied by the specified price is the market price of existing water applied by PDAM. Based on the results of research on most of the site area of Forest Protected Mount Gawalise on Ulujadi Sub District, Palu, Central Sulawesi Province, showed that the forests produce clean water for 2,989,440.00 liters / day, equivalent to 2989.44 m3 / day utilized by the area of Sub District Ulujadi and surroundings in order to fulfill water needs. By calculating water price of Rp. 3207 obtained from the average price of water taps set in 2014, 2015 and 2016, and with the water yield of 2989.44 m 3 / day of the obtained value of the produced water Protected ForestÂ  Mount Gawalise is Rp. 9,587,134.08 / day or Rp. 3,499,303,939.20 / year. Thus based on the above calculation result, the value of the function Hydrological Forest Protected Areas Mount Gawalise amounted to 3,499,303,939.20 / year, for an area of 4,024 hectares of forest area, or Rp. 869,608.33 / hectare / year.